Systematic review and meta-analyses of risk factors for childhood overweight identifiable during infancy - Weng, Stephen Franklin; Redsell, Sarah A.; Swift, Judy A.; Yang, Min; Glazebrook, Cristine P. (BMJ Group, 2012)
Objective To determine risk factors for childhood overweight that can be identified during the first year of life to facilitate early identification and targeted intervention. Design Systematic review and meta-analysis. Search strategy Electronic database search of MEDLINE, EMBASE, PubMed and CAB Abstracts. Eligibility criteria Prospective observational studies following up children from birth for at least 2 years. Results Thirty prospective studies were identified. Significant and strong independent associations with childhood overweight were identified for maternal prepregnancy overweight, high infant birth weight and rapid weight gain during the first year of life. Meta-analysis comparing breastfed with non-breastfed infants found a 15% decrease (95% CI 0.74 to 0.99; I2=73.3%; n=10) in the odds of childhood overweight. For children of mothers smoking during pregnancy there was a 47% increase (95% CI 1.26 to 1.73; I2=47.5%; n=7) in the odds of childhood overweight. There was some evidence associating early introduction of solid foods and childhood overweight. There was conflicting evidence for duration of breastfeeding, socioeconomic status at birth, parity and maternal marital status at birth. No association with childhood overweight was found for maternal age or education at birth, maternal depression or infant ethnicity. There was inconclusive evidence for delivery type, gestational weight gain, maternal postpartum weight loss and ‘fussy’ infant temperament due to the limited number of studies. Conclusions Several risk factors for both overweight and obesity in childhood are identifiable during infancy. Future research needs to focus on whether it is clinically feasible for healthcare professionals to identify infants at greatest risk.